Voice/data integration over ethernet network. - Mohd Ali, Borhanuddin (1990)
The utilisation of Packet Switched network for transporting voice besides data has attracted a lot of attention but substantial modifications and enchancements will have to be incorporated on to the simple public data network to take care for this need. In the case of Local Network Area (LAN), where there is a wide bandwidth, low delay, and resilience to interference, the transportation of voice over the same network as data, is more straight forward. The augmentation of voice services over LAN means increased productivity and economy. This paper describes the development of an experimental Packet Voice Terminal (PVT) based on a PC to integrate voice over data in an Ethernet LAN. An ADCPM based codec was developed to digitize and encode speech to 32 kb/s, which was subsequently transmitted to the network by means of an intelligent LAN adapter. Simulated tests on the voice by transmitting a binary file has indicated that voice can be transmitted over the LAN provided a suitable communication protocol to handle real time communication is incorporated.